Error rate performance analysis of multiantenna MC DS-CDMA system over Î·-Î¼ Frequency selective fading channels with arbitrary parameters - Mark Amok, J.O. (Elsevier GmbH, 2016)
Wireless communication channels have harmful impact on the performance of the wireless communication systems due to the severe influences of multipath fading, path loss, shadowing, intentional and unintentional interference, and noise, respectively. In this paper, we investigate the performance of the orthogonal multicarrier direct sequence code division multiple access (MC DS-CDMA) system coupled with multiple input multiple output (MIMO) system operating over independent nonidentically distributed (i.ni.d) Î·-Î¼ multipath fading channels in terms of average error probability. Based on moment generating function (MGF) and probability density function (PDF) approaches, closed form expressions for average error probability of binary phase shift keying (BPSK), multilevel phase shift keying (MPSK), and square M-ary quadrature amplitude modulation (MQAM) schemes are derived and expressed in terms of Appell's hypergeometric functions and Lauricella's multivariate hypergeometric functions. The numerical results show that the effects of arbitrary fading parameters, decaying power factor (d), and signal constellation size on the system performance can be reduced using spatial and temporal path diversities. We validate the correctness of the analytical approaches using Monte Carlo simulation techniques. Â© 2016 Elsevier GmbH.